SURVIVAL AND PROGNOSIS OF PATIENTS WITH CUTANEOUS MELANOMA ON EXTREMITIES - Noveski, Lazo; Matveeva, Niki; Mirchevska, Elizabeta; Dzonov, Boro; Zhivadinovik, Julija; Ginovki, Vladimir (Journal of Morphological Sciences, 2018)
Advanced melanoma is an aggressive, deadly disease and has a high detrimental impact on patients and society, primarily due to premature death. The aim of this study was to present the overall survival (OS) in cutaneous melanoma patients  with upper and lower extremities primary tumor site, and to obtain as accurate as possible an estimation of survival for these patients. A total of 100 patients with primary malignant skin melanoma on the extremities, clinically negative and clinically positive regional lymph nodes metastasis with no evidence of distant disease were analyzed. Five and 10-year overall survival were calculated with log rank analysis to determine significant differences. Prognostic factors were evaluated using Cox proportional hazard analysis. Five-year and 10-year overall survival of all patients included in the study was 72.7% and 45%, respectively. Ten-year OS of patients with clinically unpalpable nodal metastases, but pathologically evident, was 76.9% compared to 20.5% in patients with clinically palpable nodal metastases. In patients with positive regional lymh nodes metastasis,  regional lymph nodes tumor burden was dominant predictor of overall survival in a model based on age, gender, localization of the primary tumor, regional lymph nodes tumor burden and N categorization of the patients.  Macrometastatic regional lymph nodes tumor burden increased the hazard ratio of death   by 4.26 times compared to  micrometastatic regional lymph nodes tumor burden. Our results highlight the importance of nodal status early diagnosis as well as the necessity for individual approach to each patient.